1996
DOI: 10.2172/176772
|View full text |Cite
|
Sign up to set email alerts
|

Waste mixing and diluent selection for the planned retrieval of Hanford Tank 241-SY-102: A preliminary assessment

Abstract: Portions of this document rrmy be iIlegible in electronic image products. Images are produced from the best available original docmnent. SummaryThis preliminary assessment documents a set of analyses that were performed to determine the potential for Hanford waste Tank 241-SY-102 waste properties to be adversely affected by mixing the current tank contents or by injecting additional diluent into the tank during sludge mobilization. As a part of this effort, the effects of waste heating that will occur as a res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 9 publications
2
10
0
Order By: Relevance
“…The typical values of the yield stress for the DSTs when a ball rheometer was used are in the -200 Pa range and consistent with the values based on the Poisson's ratio approximations (Stewart et al 1996). Onishi et al (1996) also report a value of 2.7 Pa for the yield stress of the waste. This measurement was performed in a hood with a rotational device using a cone-and-plate sensor.…”
Section: Erosion or Failure Of Sludgesupporting
confidence: 81%
See 4 more Smart Citations
“…The typical values of the yield stress for the DSTs when a ball rheometer was used are in the -200 Pa range and consistent with the values based on the Poisson's ratio approximations (Stewart et al 1996). Onishi et al (1996) also report a value of 2.7 Pa for the yield stress of the waste. This measurement was performed in a hood with a rotational device using a cone-and-plate sensor.…”
Section: Erosion or Failure Of Sludgesupporting
confidence: 81%
“…They also measured the shear strength of the same material using a shear vane rheometer and found that in most cases the shear strength was lower than the tensile strength but closer to the tensile strength than to the yield stress. Extensive measurements of the compressive yield strength are not available other than what is presented by Onishi et al (1996). They found that the yield in the compressive mode for SY-102 sludge is approximately 8000 Pa.…”
Section: Erosion or Failure Of Sludgementioning
confidence: 99%
See 3 more Smart Citations